FEATURES OF THE IMPLEMENTATION OF THE ENTERPRISE'S MARKETINGPRODUCT POLICY IN MODERN CONDITIONS - PYVOVAROV, Serhii; PEREVOZOVA, Iryna; KHOLODNYI, Gennadii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the study of the features of implementing an enterprise's marketing product policy in modern conditions.It has been established that the formation and implementation of the enterprise's marketing product policy in modern conditions is an extremely important and multifaceted process that requires considering a wide range of external and internal factors. In the modern world, which is characterized by digitalization, globalization, innovation, and the growth of environmental awareness, enterprises face numerous challenges. However, these challenges also create new development opportunities.It has been proven that flexibility and adaptation are the main conditions for a business's survival and development. Enterprises must constantly analyze the market, anticipate changes, and respond quickly to them.It has been determined that innovation and the introduction of new technologies are becoming the main drivers of competitiveness. Those who invest in research and development receive long-term benefits.It has been substantiated that consumer orientation is the central link in modern product policy. Attention to customer needs, product personalization, and a high level of service help gain consumer trust and loyalty. Digitalization opens up new channels for interaction with customers but also requires investments in digital infrastructure and data protection.It has been confirmed that environmental friendliness and social responsibility are becoming not just trends but mandatory elements of modern business. Implementing sustainable development principles increases brand trust.Therefore, an effective marketing product policy combines strategic vision, an innovative approach, and adaptation to environmental conditions. Enterprises that skillfully manage their product policy have a high chance of not only surviving but also taking leading positions in the market, even in the most difficult conditions.
Keywords: business goals; innovation; competition; marketing; product policy; enterprise; transformation; digital marketing